Nylon material applied to new energy vehicle thermal management system resistant to freezing liquid

By treating the glass fiber surface with epoxy siloxane and selecting specific compatibilizers, the interfacial bonding force between nylon materials and glass fiber is enhanced, solving the problem of nylon materials being prone to failure in high-temperature coolants. This achieves high-performance coolant resistance and mechanical properties, making it suitable for components in the thermal management system of new energy vehicles.

CN119842225BActive Publication Date: 2026-11-03SHANGHAI PRET COMPOSITES +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411978023.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2026-11-03
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing technologies for studying the coolant resistance of nylon materials mainly focus on reducing water absorption and improving the stability of molecular structure, but they do not adequately improve the interfacial interaction between nylon resin and glass fiber. This leads to easy failure in high-temperature coolants and fails to meet the high-performance requirements of thermal management systems for new energy vehicles.

Method used

By treating the glass fiber surface with epoxy siloxane and selecting epoxy cyclohexyl-cage polysilsesquioxane as a compatibilizer, combined with triphenyl phosphate ketone hexamer and potassium iodide complex as antioxidants, the interfacial bonding force between nylon material and glass fiber is enhanced, and the material's resistance to refrigerants is improved.

Benefits of technology

The prepared nylon material maintains excellent mechanical properties and long-term thermo-oxidative aging performance in high-temperature coolants, making it suitable for components in the thermal management system of new energy vehicles and meeting the requirements for coolant resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0005220885380000031
    Figure BDA0005220885380000031
Patent Text Reader

Abstract

The application discloses a kind of applied in new energy automobile heat management system freeze-resistant liquid nylon material and preparation method thereof, the freeze-resistant liquid nylon material is according to the following raw material composition by weight percentage: nylon resin: 37-89.98%;Modified glass fiber: 10-55%;Compatibilizer: 0.01-5%;Antioxidant: 0.01-1%;Other additives: 0-2%;Glass fiber surface is treated with epoxy siloxane solution containing on glass fiber surface, sizing agent mass fraction>0.3%.The nylon material prepared by the application has excellent mechanical properties, long-term thermal-oxidative aging performance and freeze-resistant liquid performance, and can be used for automobile heat management system PTC outer plate, thermostat, water valve and other components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials, and in particular to a nylon material resistant to refrigerant used in the thermal management system of new energy vehicles. Background Technology

[0002] High temperatures increase the risk of engine and transmission failure in gasoline-powered vehicles, while low temperatures increase drag and fuel consumption. Pure electric vehicles are prone to thermal runaway in high temperatures and have poor discharge performance in low temperatures. Therefore, automotive thermal management systems play a crucial role in ensuring the functional safety and lifespan of vehicles. The main function of an automotive thermal management system is to ensure that different components operate at appropriate temperatures through heat dissipation, heating, and insulation.

[0003] Traditional gasoline-powered vehicles' thermal management systems include engine / mechanical box cooling, passenger compartment air conditioning, and intake thermal management. Pure electric vehicles' thermal management systems encompass the thermal management of the three core electrical systems (battery, motor, and electronic control system) and the passenger compartment. Automotive thermal management systems are assembled from upstream components such as water pumps and condensers, providing functional safety and lifespan assurance for the entire vehicle downstream. The thermal management systems of pure electric vehicles have undergone significant changes in coverage and implementation compared to those of gasoline-powered vehicles, placing higher demands on the energy efficiency and safety of components. The functionality and value increment of products such as valves, heat exchangers, pumps, pipelines, and PTCs are further enhanced, leading to more stringent material requirements for components. Nylon materials possess excellent high-temperature resistance, high strength, good coolant resistance, and processing performance, making them the preferred material for components such as PTC outer plates, thermostats, and water valves in thermal management systems.

[0004] Chinese patent CN202323234385.1 discloses a new application of dendritic polyamide-amine polymers. Dendritic polyamide-amine polymers can reduce the proportion of water and / or alcohol attack reactions on terminal carboxyl groups, thereby improving the hydrolysis and alcoholysis resistance of polyamide compositions. At the same time, the dense active functional groups on the surface of dendritic polyamide-amine polymers can establish cross-linking structures between different polyamide molecular chains, improve melt strength and uniformity, and ensure melt flowability. This makes it easy for bubbles to grow and not easily break during the mucell molding process of polyamide compositions, forming a uniform and dense microporous structure, maintaining a high performance retention rate of polyamide compositions, and obtaining finished parts with good appearance. Chinese invention patent CN202211241820.0 discloses a hydrolysis- and alcoholysis-resistant reinforced nylon material and its preparation method. Through the compounding of raw materials and the addition of heat stabilizers and hydrolysis-resistant agents, a high-performance hydrolysis-resistant reinforced nylon material is obtained. This material retains over 70% of its tensile strength even after continuous immersion in ethylene glycol antifreeze at 135°C for more than 120 hours, thus preventing the accelerated hydrolysis of nylon materials in high-temperature and humid environments, which could lead to performance degradation and potential hazards. Chinese patent CN202011278992.6 discloses an alcoholysis-resistant reinforced PA6T material and its preparation method. The compatibilizer is a styrene-N-phenylmaleimide copolymer, which can capture alcohols invading the material's interior, providing active defense and improving the adhesion between the glass and the matrix resin, thus giving the material excellent alcoholysis resistance. Related technologies have been studied to some extent in terms of the effects of dendritic polymers, hydrolysis-resistant additives, and compatibilizers on the alcoholysis resistance of nylon materials. However, the research content is limited to reducing the water absorption of nylon, increasing the crosslinking of polyamides, and improving the stability of the molecular structure to improve the antifreeze resistance of nylon materials. Antifreeze failure usually occurs when the interface between nylon resin and glass fiber is damaged in high-temperature antifreeze. There is relatively little research on the influence of the resin-glass fiber interface and the improvement of the heat resistance of nylon materials on the antifreeze resistance of nylon materials. Summary of the Invention

[0005] The purpose of this invention is to provide a coolant-resistant nylon material for use in the thermal management system of new energy vehicles. Through additives in the formulation design, the nylon material achieves both heat resistance and coolant resistance. Simultaneously, the effects of compatibilizers and glass fiber interface treatment on the coolant resistance of the nylon material are investigated. This is of great significance for the research of nylon materials suitable for automotive thermal management system components. The nylon material prepared by this method can meet the performance requirements of thermal management system components.

[0006] The objective of this invention is achieved through the following technical solution:

[0007] A refrigerant-resistant nylon material for use in the thermal management system of new energy vehicles is composed of the following raw materials by weight percentage: nylon resin: 37-89.98%; modified glass fiber: 10-55%; compatibilizer: 0.01-5%; antioxidant: 0.01-1%; the glass fiber surface is sized with an epoxy siloxane solution, and the sizing agent mass fraction is >0.3%.

[0008] The modified glass fiber has an alkali content of <0.8% and a bulk density of 0.6-0.8 g / cm³. 3 Monofilament fiber diameter: 7-13μm, chopped length: 2-5mm, moisture content ≤0.05%.

[0009] The nylon resin is PA66 chips with reactive amino groups at the ends. The PA66 chips have a melting point of 255-265℃, a relative viscosity of 2.6±0.6, and a terminal amino group content of ≥90mmol / kg.

[0010] The sizing agent solution contains 1%-10% epoxysiloxane by mass, and the density of epoxysiloxane is 1.050±0.06 g / cm³. 3 It contains 16.9% silicon, has an epoxy equivalent of 206.3, an epoxy value of 0.48 / 100g, and its general structural formula is as follows:

[0011]

[0012] The compatibilizer is an epoxycyclohexyl-cage polysilsesquioxane with a density of 1.31 ± 0.1 g / cm³. 3 It has an epoxy equivalent of 177.2, an epoxy value of 0.56 / 100g, a silicon content of 15.8%, and the following general structural formula:

[0013]

[0014] The antioxidant is a complex of triphenyl phosphate hexamer and potassium iodide, with a ratio of 9:1 to 1:9, forming a reducing coordination ion.

[0015] The other additives may be one or more of lubricants and colorants.

[0016] The preparation method of the above-mentioned antifreeze nylon material used in the thermal management system of new energy vehicles includes the following steps:

[0017] (1) Weigh out the dried raw materials according to the formula ratio;

[0018] (2) Mix the nylon resin, compatibilizer, antioxidant, and other additives evenly using a high-speed mixer;

[0019] (3) Weigh the modified glass fiber according to the proportion;

[0020] (4) The above-mentioned resin and additive mixture is added through the main feed port of the twin-screw extruder, and the modified glass fiber is added through the side feed port of the twin-screw extruder. After melt extrusion, granulation and drying processes, the above-mentioned refrigeration-resistant nylon material is obtained.

[0021] The above-prepared coolant-resistant nylon material can be applied to components such as PTC outer panels, thermostats, and water valves in automotive thermal management systems.

[0022] The advantage of this invention lies in the fact that the nylon material prepared through glass fiber pretreatment and formulation design meets the requirements of automotive thermal management system components for mechanical properties, coolant resistance, and long-term thermo-oxidative aging performance. Based on the structural characteristics of nylon material and its coolant failure mechanism, the interfacial reaction between the modified glass fiber (prepared by attaching epoxy siloxane to the glass fiber surface) and the nylon resin increases the compatibility between the glass fiber and the resin. In the formulation design, epoxy cyclohexyl-cage polysilsesquioxane was selected as a compatibilizer, and the end groups of the nylon resin were limited. Through the combined effects of "like-like compatibility" and "chemical compatibilization," the interfacial bonding force between nylon and glass fiber was increased. The "hydrophobic" effect of silicon in the compatibilizer further enhances the coolant resistance of the nylon material. In the formulation design, this invention selected a triphenylphosphine ketone hexamer and a potassium iodide complex as functionalizing agents; the two, when combined, form a reducing coordination ion. Coordinating ions have the lowest potential and higher reducing power, and can preferentially react with oxygen, free radicals, etc., further protecting the polymer from oxidative damage and improving the performance retention rate of nylon materials in high-temperature cryogenic liquids. At the same time, triphenylphosphine ketone hexamer has hydrophobicity and "steric hindrance" effect, and will not fail due to extraction by the cryogenic liquid environment. The nylon material prepared by this invention has excellent mechanical properties, long-term thermo-oxidative aging performance and cryogenic liquid resistance.

[0023] The beneficial effects of this invention are as follows:

[0024] 1) In this invention, epoxy siloxane is attached to the surface of glass fiber to prepare glass fiber and nylon resin with better interfacial bonding and compatibility through chemical bonding. The prepared nylon material has excellent resistance to cold liquid and mechanical properties.

[0025] 2) The formulation design selected epoxy cyclohexyl-cage polysilsesquioxane as a compatibilizer. Through the combined effect of "like compatibilizer" and "chemical compatibilization", the interfacial bonding force between nylon and glass fiber was increased. The "hydrophobic" effect brought by silicon element in the compatibilizer further improved the antifreeze performance of nylon material.

[0026] 3) Based on the type of active groups in the glass fiber surface treatment agent and compatibilizer, the present invention limits the type and content of end groups in the nylon resin selected in the formulation design. This is beneficial to the formation of chemical bonds between the nylon resin and glass fiber interface through the reaction of active groups during the preparation of the cryogenic nylon material, thereby increasing the interfacial bonding force between nylon and glass fiber and thus increasing the cryogenic resistance of the nylon material.

[0027] 4) In the formulation design of this invention, triphenyl phosphate ketone hexamer and potassium iodide complex were selected as functionalizing agents. The two are combined to form a reducing coordination ion. The coordination ion has the lowest potential and higher reducing power, and can preferentially react with oxygen, free radicals, etc., further protecting the polymer from oxidative damage and improving the performance retention rate of nylon materials in high-temperature cryogenic liquids. At the same time, triphenyl phosphate ketone hexamer has hydrophobicity and "steric hindrance" effect, and will not be extracted and degraded by the cryogenic liquid environment.

[0028] 5) The preparation method of this invention is simple, and the prepared nylon material takes into account mechanical properties, long-term thermo-oxidative aging performance and coolant resistance, making it suitable for automotive thermal management system components and providing a material solution for thermal management system components of new energy vehicles.

[0029] The above-mentioned beneficial effects enable nylon materials to achieve excellent mechanical properties, long-cycle thermo-oxidative aging performance, and resistance to refrigerants. Detailed Implementation

[0030] To make the technical problem to be solved, the technical solution, and the intent of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0031] The embodiments and comparative examples of the present invention use the following materials, but are not limited to the following materials:

[0032] Nylon resin, commercially available

[0033] Nylon resin PA66, trade name EPR27, is produced by Shenma Engineering Plastics Co., Ltd.

[0034] Glass fiber, trade name ECS301HP-3, produced by Chongqing International Composite Materials Co., Ltd.

[0035] Modified glass fiber, homemade;

[0036] Compatibilizer, epoxycyclohexyl-cage polysilsesquioxane, commercially available;

[0037] Antioxidant triphenylphosphine ketone hexamer, commercially available;

[0038] Potassium iodide, an antioxidant, is commercially available.

[0039] Antioxidant H3386, produced by BRUGGOLEN;

[0040] Antioxidant 1098, a hindered phenolic antioxidant, is commercially available.

[0041] Antioxidant 168, a phosphite antioxidant, is commercially available.

[0042] Processing aid. Trade name LYSI-100E, manufactured by Chengdu Silike Technology Co., Ltd.

[0043] Masterbatch, product name PA6-2015, commercially available;

[0044] Preparation methods of Examples 1-5 and Comparative Examples 1-5:

[0045] Preparation method of cryogenic nylon material:

[0046] (1) Weigh out the dried raw materials according to the formula ratio; mix the nylon resin, compatibilizer, antioxidant and other additives evenly with a high-speed mixer and set aside; weigh out the modified glass fiber according to the formula ratio and set aside.

[0047] (2) The above-mentioned resin and additive mixture is added through the main feed port of the twin-screw extruder, and the modified glass fiber is added through the side feed port of the twin-screw extruder. After melt extrusion, granulation and drying processes, the above-mentioned refrigeration-resistant nylon material is obtained.

[0048] Preparation of test strips for cryogenically resistant nylon materials:

[0049] The above materials were dried in a forced-air drying oven at 120℃ for 4 hours, and then injection molded into standard specimens at an injection molding temperature of 280-330℃. The prepared mechanical property specimens were then conditioned in a standard laboratory environment (23℃, 50%RH) for 24 hours before testing.

[0050] Test methods for each performance indicator:

[0051] Tensile properties: According to ISO 527 method, specimen size: 170*10*4mm, test speed 5mm / min.

[0052] Bending performance: According to ISO 178 method, the sample size is 80*10*4mm, and the test speed is 2mm / min.

[0053] Notched impact performance: according to ISO 179 method, spline size: 80*10*4mm.

[0054] Heat distortion temperature: according to ISO 75 method, specimen size: 80*10*4, test conditions: 1.8MPa.

[0055] Tensile strength retention rate (thermal-oxidative aging): 1) The tensile strength of the injection-molded specimen after conditioning in a laboratory environment according to ISO 527 is recorded as the tensile strength before aging; 2) After placing the standard test specimen in a 180℃ oven for 3000h, it is then conditioned in a laboratory environment (23℃, 50%RH) for 24h, and the tensile strength is recorded as the tensile strength after aging - A according to ISO 527 method; 3) Tensile strength retention rate - A = tensile strength before aging / tensile strength after aging - A * 100%.

[0056] Tensile strength (resistance to freezing liquid): The standard test specimen was placed in a 130°C, 50% ethylene glycol solution for 1008 hours, then removed and cooled to room temperature. After conditioning in a laboratory environment (23°C, 50% RH) for 12 hours, the tensile strength was tested according to ISO 527 method.

[0057] Table 1: Composition and properties of nylon materials in Examples 1-5 and Comparative Examples 1-5

[0058]

[0059]

[0060] As can be seen from the results of the examples and comparative examples in Table 1, the content of amine-terminated nylon resin, glass fiber pretreatment, compatibilizer, and antioxidant in the formulation are key factors affecting the cryogenic resistance and long-term thermo-oxidative aging performance of nylon materials. Examples 3-5 and Comparative Example 1 show that the introduction of epoxy cyclohexyl-cage polysilsesquioxane into the formulation design can improve the mechanical properties, cryogenic resistance, and thermo-oxidative aging performance of nylon materials. Examples 3, Comparative Examples 1, and Comparative Example 4 show that epoxy siloxane surface pretreatment of glass fiber has a positive effect on improving the cryogenic resistance of nylon materials. This is because epoxy siloxane increases the interfacial bonding force between nylon and glass fiber through the combined effects of "like dissolves like" and "chemical compatibilization." The "hydrophobic" effect of silicon in epoxy siloxane further enhances the cryogenic resistance of nylon materials. As can be seen from Examples 3 and 5, the high-end amino groups of nylon resin can improve the thermo-oxidative aging performance and coolant resistance of nylon materials. This is because the reaction of the terminal amino groups with the maleic anhydride groups of the glass fiber surface and the compatibilizer increases the interfacial bonding force between the nylon resin and the glass fiber surface. Examples 1-3 and 2-3 show that the antioxidant system used in this invention is more effective than the organic copper salt, hindered phenol, and phosphite systems in terms of coolant resistance and long-term heat resistance. This is because the antioxidant system of this invention has strong reducing properties, and the organic copper and organic halides can avoid the risk of antioxidant failure due to metal ion extraction by the coolant in coolant, thus improving the coolant resistance of nylon materials. Compared with traditional antioxidants, the heat resistance and coolant resistance of nylon materials are significantly improved. The nylon material prepared by this invention has excellent coolant resistance, long-term heat resistance, and mechanical properties, and can be used in automotive thermal management system PTC outer panels, thermostats, water valves, and other components.

Claims

1. A refrigerant-resistant nylon material for use in the thermal management system of new energy vehicles, characterized in that, Raw materials according to the following weight percentage Composition: Nylon resin: 37-89.98%; Modified glass fiber: 10-55%; Compatibilizer: 0.01-5%; Antioxidant: 0.01-1%; other additives; modified glass fiber is obtained by sizing the glass fiber surface with an epoxy siloxane solution, with the sizing agent mass fraction >0.3%; The nylon resin is PA66 chips with reactive amino groups at the ends. The PA66 chips have a melting point of 255-265℃, a relative viscosity of 2.6±0.6, and a terminal amino group content of ≥90mmol / kg. The sizing agent solution contains 1%-10% by mass of epoxysiloxane, and the density of epoxysiloxane is 1.050±0.06 g / cm³. 3 The epoxy equivalent is 206.3, the epoxy value is 0.48 / 100g, and the structure is as follows: ; The compatibilizer is an epoxycyclohexyl-cage polysilsesquioxane with a density of 1.31 ± 0.1 g / cm³. 3 It has an epoxy equivalent of 177.2, an epoxy value of 0.56 / 100g, a silicon content of 15.8%, and the following general structural formula: ; The other additives are one or more of the following: lubricants and colorants.

2. The refrigerant-resistant nylon material for use in the thermal management system of new energy vehicles according to claim 1, characterized in that: The modified glass fiber has an alkali content of <0.8% and a bulk density of 0.6-0.8 g / cm³. 3 Monofilament fiber diameter: 7-13μm, chopped length: 2-5mm, moisture content ≤0.05%.

3. The refrigerant-resistant nylon material for use in the thermal management system of new energy vehicles according to claim 1, characterized in that: The antioxidant is a compound of triphenyl phosphate hexamethylene hexamethylene and potassium iodide, with a ratio of 9:1 to 1:

9.

4. The method for preparing the refrigerant-resistant nylon material for use in the thermal management system of new energy vehicles as described in any one of claims 1-3, characterized in that, Includes the following steps: Weigh out the dried raw materials according to the formula ratio; The nylon resin, compatibilizer, antioxidant, and other additives are mixed evenly using a high-speed mixer. Weigh the modified glass fiber according to the specified ratio; The above-mentioned resin and additive mixture is fed into the main feed port of a twin-screw extruder, and the modified glass fiber is fed into the side feed port of the twin-screw extruder. After melt extrusion, granulation and drying processes, the above-mentioned freeze-resistant nylon material is obtained.

5. The application of the antifreeze nylon material in the thermal management system of new energy vehicles as described in any one of claims 1-3 in the direction of PTC outer plate, thermostat or water valve components of the automotive thermal management system.

Citation Information

Patent Citations

  • A resistant alcoholysis reinforced PA6T material and its preparation method

    CN112592583B

  • Hydrolysis-resistant alcoholysis-resistant reinforced nylon material and preparation method thereof

    CN115710429A

  • Low-carbon recyclable nylon pipeline for thermal management system

    CN221476399U

  • Environment-protective halogen-free glass fiber reinforced polyamide flame retardant

    CN107629450A

  • Fluorine-containing organosilicon epoxy monomer and preparation method thereof, application of fluorine-containing organosilicon epoxy monomer in preparation of imprinting adhesive, imprinting adhesive and preparation method thereof, and imprinting method

    CN116655681A